2013
DOI: 10.1016/j.polymertesting.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Prototype and methodology for the characterization of the polymer-calibrator interface heat transfer coefficient

Abstract: The extrusion of technical thermoplastics profiles generally uses a dry calibration/cooling system, composed by one or several calibrators in series. One of the major difficulties to be faced when modelling this important stage is an adequate prescription of the heat transfer coefficient, h interface , between the plastic profile surface and the cooling medium, which must include the effect of the interface contact resistance. This is the motivation that led the present research team to develop a prototype cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…Such a coefficient highly depends on several conditions such as the contact resistance at the interface, the roughness of the material as it is shown in Figure 1 while temperature is assumed to be discontinuous at the interface to take into account the large gradient at a microscopic level. Due to the sensitivity of the cooling process with respect to the thermal transfer coefficient, an accurate model and numerical scheme are mandatory to provide approximations leading to a correct evaluation of the transfer coefficient [1] that ranges between 10 and 10000 W/(m 2 K) according to its location in the calibration system [4].…”
Section: Introductionmentioning
confidence: 99%
“…Such a coefficient highly depends on several conditions such as the contact resistance at the interface, the roughness of the material as it is shown in Figure 1 while temperature is assumed to be discontinuous at the interface to take into account the large gradient at a microscopic level. Due to the sensitivity of the cooling process with respect to the thermal transfer coefficient, an accurate model and numerical scheme are mandatory to provide approximations leading to a correct evaluation of the transfer coefficient [1] that ranges between 10 and 10000 W/(m 2 K) according to its location in the calibration system [4].…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent this problem, the authors of this work have been developing several numerical codes to deal with the heat transfer at the calibration/cooling unit, and concluded that one of the most influential parameters, required as input in the numerical codes, is the heat transfer coefficient at the polymer-calibrator interface, h int . In turn, this coefficient highly depends on process conditions (such as the roughness of the calibration material, the extrusion velocity, and the degree of vacuum, among others) and may vary within a wide range [1]. Therefore, in the simulations of the calibration/cooling stage, accurate values of h int , determined in well controlled conditions, should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the simulations of the calibration/cooling stage, accurate values of h int , determined in well controlled conditions, should be considered. For this sake, a prototype calibration/cooling system, previously presented in [1], was developed, being the numerical codes developed for simulation purposes also used to compute, by inverse engineering, h int . However, the determination of this coefficient resorting to the referred prototype faces some other difficulties since an accurate model and numerical scheme are mandatory to provide approximations leading to a correct valuation of this coefficient [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main limitation of this code is that it can only handle structured meshes, and therefore it cannot cope with complex geometry profiles. The most recent contributions for the cooling stage modelling are the works of Mousseau et al [17] and Carneiro et al [18], who produced experimental devices able to quantify the heat transfer coefficient (or contact resistance) at the profilecalibrator interface. This heat transfer coefficient has a significant role on the profile extrusion cooling stage performance [13], being its detailed characterization essential to accurately model the system temperature distribution.…”
Section: Introductionmentioning
confidence: 99%